High-index dielectric meta-materials for near-perfect broadband reflectors. (13th April 2016) - Liu, Zhengqi; Liu, Xiaoshan; Wang, Yan; Pan, Pingping
Abstract: All-dielectric meta-materials offer a potential alternative to plasmonic meta-materials at optical frequencies. Herein, we take advantage of loss-less as well as simple unit cell geometry to demonstrate near-perfect broadband reflectors made from all-dielectric materials. These near-perfect reflectors, consisting of high-index cross-shaped resonators ( n = 3.5, Si), operating in the telecommunications bands, exhibit novel optical properties including polarization-independent, wide-angle near-unity reflection. The average reflectance is exceeding 98% at the wavelength range from 1.261 μ m to 1.533 μ m. At 1.310 μ m, the average reflectance ( R ) reaches 99.7%, surpassing the reflectance of metallic mirrors. A near-perfect super-broadband reflection spectrum with bandwidth of 0.330 μ m ( R > 98%) is achieved for a system with a higher index dielectric resonator array ( n = 4.0, Ge). Moreover, the optical properties of the reflector provide high scalability across the wavelength range via tuning of dielectric resonators. The whole structure, with common triple-layer features, can be mass-produced using standard lithography methods and deposition techniques. These optical and structural features make the proposed near-perfect broadband reflectors feasible avenues for manipulating light in important applications in spectroscopy, photovoltaics and light emission.